Practical C programming solutions for modern C developers to create efficient and well-structured programs - Harwani, B. M. (Packt Publishing, 2020)
Practical C Programming will teach you how to deal with C and its idiosyncrasies, and benefit from its new features, through bite-sized recipes. Each recipe in the book addresses a specific problem through a discussion that reveals and explains the solution to the recipe. This book will teach all you need to know to become a better C programmer.